The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/s2542-5196(18)30188-8
|View full text |Cite
|
Sign up to set email alerts
|

Restructuring physical micro-environments to reduce the demand for meat: a systematic review and qualitative comparative analysis

Abstract: SummaryBackgroundReducing meat consumption could help to protect the natural environment and promote population health. Interventions restructuring physical micro-environments might help to change habitual behaviour. We synthesised the scientific evidence pertaining to whether, and which, interventions restructuring physical micro-environments effectively reduce the demand for meat.MethodsWe did a systematic review of quantitative studies evaluating the effectiveness of interventions restructuring physical mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
103
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 178 publications
(111 citation statements)
references
References 52 publications
4
103
1
1
Order By: Relevance
“…Our results indicate that meal selection is neither fixed nor random, but rather is partially determined by availability. These results suggest that increasing the proportion of vegetarian options may have a larger effect than many other choice architecture interventions included in a recent systematic review on meat selection and consumption (13): In previous studies, neither restructuring food menus with different meal descriptions nor positioning meat in less prominent positions reduced meat uptake. Providing US and UK participants with meat substitutes, recipes, and educational materials led to large reductions in meat consumption (13): a 40% reduction in red and processed meat (31), a 54% reduction in spending on meat (32), and a 70% reduction in meat consumed (33).…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Our results indicate that meal selection is neither fixed nor random, but rather is partially determined by availability. These results suggest that increasing the proportion of vegetarian options may have a larger effect than many other choice architecture interventions included in a recent systematic review on meat selection and consumption (13): In previous studies, neither restructuring food menus with different meal descriptions nor positioning meat in less prominent positions reduced meat uptake. Providing US and UK participants with meat substitutes, recipes, and educational materials led to large reductions in meat consumption (13): a 40% reduction in red and processed meat (31), a 54% reduction in spending on meat (32), and a 70% reduction in meat consumed (33).…”
Section: Discussionmentioning
confidence: 78%
“…While many recent papers have stressed the importance of reducing meat consumption (1)(2)(3)36), very few studies have tested which interventions might work. For example, a recent systematic review found only 18 studies with 11,290 observations that tested how changing some aspect of choice architecture could reduce meat consumption (13). Our studies have 94,644 observations from months of robust, individual-level data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A protocol for this systematic review was published on PROSPERO [ 21 ]. This review includes studies evaluating interventions targeting conscious determinants of human behaviour to reduce the consumption, purchase, or selection of meat, and that fulfilled the eligibility criteria outlined in Table 1 .…”
Section: Methodsmentioning
confidence: 99%